Struktur Komunitas Fitoplankton di Perairan Pesisir Pulau Siantan Kabupaten Kepulauan Anambas Provinsi Kepulauan Riau - Lani Puspita; Notowinarto Notowinarto; Rudi Gunawan (CAHAYA PENDIDIKAN, 2015)
Phytoplankton as a producers  and natural food for fish have an important role in aquatic ecosystems, thus indirectly affecting the availability of fish catches. The research was conducted at Siantan Island Coastal Area Anambas Islands District Riau Islands Province. This coastal area is one of the fishing grounds in Anambas Island. This study aims to analyze the community structure of phytoplankton at Siantan Island Coastal Area Anambas Islands District Riau Islands Province. Sampling was conducted during March and April 2012. Community structure parameters analyzed include Species Diversity Level, Species Uniformity Level, and Species Dominance Level. Data were analyzed spatially and temporally. Similarity between the sampling locations was conduted by Multivariate Analysis - Cluster. Results of data analysis showed that the phytoplankton of Bacillariophyceae Class found in the most abundant amount. Diversity Index Value indicates that the level of phytoplankton plankton community in a state of moderate. Species Uniformity Index Value and Species Dominance Index Value indicates that phytoplankton in the three sampling locations are generally in a state of uniform and no one dominates. All three sampling locations have relatively the same condition and between sampling times (morning, afternoon, and evening) are also not very different condition. Keywords: phytoplankton, coastal, Anambas Islands